ANALISIS SEMANTIK TERHADAP PESAN KEHAMPAAN DIRI DALAM LAGU “TEH HIJAU” KARYA TULUS - Lianaa, Anindya; Imas Juidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the message of self-emptiness through semantic analysis in the lyrics of the song "Teh Hijau" by Tulus. This study analyzes the denotative and connotative meanings that represent psychological conditions and the emotional messages conveyed. This study uses a qualitative descriptive method with a literature study approach. Data sources were obtained from the lyrics of the song "Teh Hijau" popularized by Tulus. The results of this study indicate that the song lyrics represent phases of emotional exhaustion, numbness (burnout), and the process of self-acceptance. The denotative meaning in the song depicts the simple routine of drinking green tea as a space to pause, while the connotative meaning contains a deep message about accepting the feeling of emptiness, making peace with loneliness, and the search for inner peace (self-healing). Thus, semantic analysis proves that the choice of words (diction) used is able to strengthen the delivery of deep emotional messages about self-emptiness to the listeners.